OBSERVATIONS ON THE DISTRIBUTION AND FLUCTUATIONS OF PLANKTON IN THE HOOGHLY-MATLAH ESTUARINE SYSTEM, WITH NOTES ON THEIR RELATION TO COMMERCIAL FISH LANDINGS - Shetty, H P C; Saha, S B; Ghosh, B B (Indian Journal of Fisheries, 2011)
OBSERVATIONS’on the plankton of the Hooghly-Matlah estuarine system were taken up in order to study its distribution and seasonal fluctuations, as part of a comprehensive study on the commercially important fish populations of the estuary. Some workers like Juday, Rich, Kemmerer and Mann (1932) and Ricker (1938) have attempted to relate fluctuations in plankton populations to the vital statistics of commercially important fishes. The significance of plankton studies in elucidating some of the probable factors responsible for fluctuations in abundance and movements of fish stocks is well known. The Hooghly-Matlah esttiarine system is of great economic importance from the fisheries point of view and a detailed study of the plankton of this estuary is expected to throw some light on the pattern of fluctuations in its fisheries.